Adenoma pleomórfico en glándulas salivares menores: reporte de tres casos en niños - Duque-Serna, Francisco Levi; Naranjo-Restrepo, Rodrigo Felipe; Alvarez-Martínez, Efraín; Valencia-Londoño, Walter Augusto (Revista Facultad de Odontología Universidad de Antioquia, 2017)
Salivary gland tumors are scarce during the first and second decades of life; when they appear in these age ranges, they are generally found in the parotid gland. Minor salivary gland tumors are even more scarce, being the pleomorphic adenoma the most common one. Most authors define the pleomorphic adenoma as an oval or round suhrnucous tumoration, unique, well delimitated, non -infiltrated, hard - elastic and painless. The covering mucous membrane remains undamaged; however secondary ulceration may occur, either due to intrinsical growth of the tumor or because of trauma; its growth is slow. When the pleomorphic adenoma shows up in the palate, a diterential diagnosis should he made along with other patologies such as those of infectious type, the non - odontogenic cysts and tumors, the odontogenic cysts and tumors and finally, the pseudotumoral lesions. Treatment for the pleomorphic adenoma is the total enucleation; Most authors suggest a wide local excision that extends at least r in outside the visible margin of the tumor. Fenestration of the soft palate may be necessary in order to obtain the required surgical margins. Only eight cases of palate pleomorphic adenoma in children have been reported in the world literature,- here we present 3 cases of pleomorphic adenoma found in palate minor salivary glands of male sex patients: one in an 8 year old child and two in 15 year old youngsters.